Vertical distribution of mesozooplankton biomass in relation to oxygen minimum layer in the Andaman Sea - Madhu, N V; Jyothibabu, R; Ramu, K; Sunil, V; Gopalakrishnan, T C; Nair, K K C (Indian Journal of Fisheries, 2011)
Mesozooplankton biomass in the upper 1000m of the Andaman Sea was studied during February 1999 providing baseline information on stratification of mesozooplankton of the area. The distribution of mesozooplankton biomass is related to the oxygen minimum layer (<0.1 ml/litre). The biomass and group wise diversity were maximum in the mixed layer (average 5 ml/100m3) and sometimes in the thermocline layer (average 4.4 ml/1003). A prominent feature was that the minimum average biomass values were confined to the depth strata of 300m-bottom of thermocline (BT) (0.9ml/100m3) where the oxygen minimum layer was more pronounced. The averages of zooplankton group percentages in the upper 1000m showed that copepoda forms the major group (81.01 %) followed by chaetognatha (6.7 %), ostracoda (4.8 %), siphonophora (1.9 %), and decapod larvae (1.3 %) and the corresponding average population densities were 4,620 /100m3, 1,201/100 m3, 104/100 m3, 102 /100m3, and 7 /100m3.